The impact of the inflow momentum on the transient roll response of a damaged ship. (1st July 2016) - Manderbacka, Teemu; Ruponen, Pekka
Abstract: Dynamics of an abrupt flooding case are studied by comparing fully dynamic and quasi-static flooding simulation methods. Transient asymmetric flooding is traditionally modelled by dividing the compartment into smaller parts with bulkheads representing different obstructions in the flooded compartment. The implications of this assumption are studied by varying the size of the opening on the dividing bulkhead. The importance of the inflooding jet to the response is shown. The jet i.e. the inflooding momentum flux is modelled as force acting on the lumped mass. When the flooded compartment does not have significant obstructions it is important to account for the inflooding momentum flux. Abstract : Highlights: The importance of the dynamic effect of the inflooding is studied. Calculation time-wise effective novel numerical method is applied. The advantages of a novel method for flooding simulation are shown. The performance of commonly used flooding simulation methods is compared. The importance of the inflooding jet to the response of the damaged ship is show.